The Affordable Care Act's Coverage Impacts in the Trump Era. (7th October 2021) - Courtemanche, Charles; Fazlul, Ishtiaque; Marton, James; Ukert, Benjamin; Yelowitz, Aaron; Zapata, Daniela
The 2016 US presidential election created uncertainty about the future of the Affordable Care Act (ACA) and led to postponed implementation of certain provisions, reduced funding for outreach, and the removal of the individual mandate tax penalty. In this article, we estimate how the causal impact of the ACA on insurance coverage changed during 2017 through 2019, the first 3 years of the Trump administration, compared to 2016. Data come from the 2011–2019 waves of the American Community Survey (ACS), with the sample restricted to non-elderly adults. Our model leverages variation in treatment intensity from state Medicaid expansion decisions and pre-ACA uninsured rates. We find that the coverage gains from the components of the law that took effect nationally—such as the individual mandate and regulations and subsidies in the private non-group market—fell from 5 percentage points in 2016 to 3.6 percentage points in 2019. In contrast, the coverage gains from the Medicaid expansion increased in 2017 (7.0 percentage points) before returning to the 2016 level of coverage gains in 2019 (5.9 percentage points). The net effect of the ACA in expansion states is a combination of these trends, with coverage gains falling from 10.8 percentage points in 2016 to 9.6 percentage points in 2019.